1993
DOI: 10.1080/02626669309492661
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration-recharge through wadi beds in arid regions

Abstract: Groundwater recharge in arid regions is intermittent and usually occurs as a result of flood flow transmission losses in dry wadi channels. Hydrograph characteristics play a dominant role in determining the amount of channel abstraction in relation to the width of the wetted perimeter and the time of inundation, and the subsequent groundwater recharge. Large variations in the magnitude of channel losses result mainly from the diversity in inflow volumes. The magnitude of groundwater recharge in relation to bed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 19 publications
4
61
0
Order By: Relevance
“…Under flood water depths of 1, 3, 5 and 10 cm, the groundwater Similar results were reported by Sorman and Abdulrazzak [24], who suggested that flood runoff volume and duration were the dominant factors influencing the cumulative infiltrated volume and recharge of shallow groundwater tables. Morin et al [1] showed the importance of the role of large and medium floods in aquifer recharge; the relative contribution of high-magnitude floods to groundwater recharge also increased, whereas medium and small floods contributed relatively less.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Under flood water depths of 1, 3, 5 and 10 cm, the groundwater Similar results were reported by Sorman and Abdulrazzak [24], who suggested that flood runoff volume and duration were the dominant factors influencing the cumulative infiltrated volume and recharge of shallow groundwater tables. Morin et al [1] showed the importance of the role of large and medium floods in aquifer recharge; the relative contribution of high-magnitude floods to groundwater recharge also increased, whereas medium and small floods contributed relatively less.…”
Section: Resultssupporting
confidence: 77%
“…These results indicated that the height of the water table rise was closely related to flood water depth; if the initial water table was deeper, the variation in the depth of the water table rise was smaller. Sorman and Abdulrazzak [24] also reported that the relationship between the ground water recharge and flood inflow volume could be represented by linear regression equations, with the correlation coefficients of 0.76, but the slope was 0.302, which was still lower than the slope related to flood recharge infiltration in our research. Note that Sorman and Abdulrazzak [24] experiments were conducted under conditions of possible surface water runoff, while our experiments were conducted in lysimeters with ponding water, with no occurrence of outflow.…”
Section: Resultsmentioning
confidence: 64%
“…Several regression equations were presented to estimate the transmission losses and recharge from a wadi-bed in Saudi Arabia [6,17]. These studies indicate that the magnitude of transmission losses and consequent recharge resulting from given upstream runoff hydrographs is a function of stream and sediment characteristics.…”
Section: Statistical and Physical Modelingmentioning
confidence: 99%
“…The aquifer underlying a wadi channel is recharged primarily by infiltration and percolation coupled with transmission loss (infiltration) in the channel during flood events [1][2][3][4][5][6][7][8][9][10][11][12]. A number of…”
Section: Introductionmentioning
confidence: 99%